Ionic Liquid Membrane for Carbon Capture and Separation. Issue 2 (3rd April 2022) - Zunita, M.; Hastuti, R.; Alamsyah, A.; Khoiruddin, K.; Wenten, I. G.
ABSTRACT: Carbon dioxide capture from industrial gases (i.e., flue gases and natural gas) is a crucial process for reducing the environmental impacts of acid gas emissions. However, carbon dioxide capture that is generally performed by amine-based solvent faces operational problems due to the properties of the solvent. Recently, ionic liquids (ILs) have emerged as promising candidates for replacing the amine-based solvent due to their low vapor pressure (near-zero), high stability, as well as tunable structure and properties. The functionalized ILs are considered superior in terms of their ease of regeneration as well as high absorption capacity and selectivity toward CO2 . Combining the functionalized ILs with membrane processes has opened up a new horizon in CO2  capture technology. This review comprehensively summarizes the latest developments in the application of ionic liquid membranes (ILMs) for CO2  capture, including supported ILMs (SILMs), poly-ILMs (PILMs), polymer-IL composite membranes, mixed-matrix-membranes,  with special attention to ILM contactors. The absorption mechanisms of CO2  in the ILs are pictured and discussed.